The mathematical communication ability based on student's self-confidence in Problem Based Learning models with brainstorming techniques - Maysaroh, Wiwit; Mulyono, Mulyono; Kurniasih, Ary Woro (Unnes Journal of Mathematics Education, 2021)
The mathematical communication ability is an important aspect that every student must have. The Facts show that mathematical communication ability and student confidence are still not optimal. One effort to overcome that is by applying PBL models with brainstorming techniques. The purpose of this study was to test the effectiveness of the PBL model with brainstorming techniques on students' mathematical communication ability, describing mathematical communication ability on PBL models with brainstorming techniques in terms of student confidence. This research uses mix method approach with a concurrent embededded model. The population of this study was class VIII of SMP Negeri 1 Ungaran in the 2018/2019 school year. The results showed that: PBL models with effective brainstorming techniques for learning as indicated by learning outcomes in aspects of mathematical communication ability achieve mastery learning individually and classically as well as the average learning outcomes in classes using PBL models with brainstorming techniques more than average learning outcomes in the classroom using the PBL model, subjects with high self-esteem can meet all indicators of mathematical communication ability, on subjects with moderate self-confidence only able to meet indicators explaining ideas, situation and mathematical relationship at writing and indicators listening, discussing and writing about mathematics. Whereas for subjects with low levels of self confidence have not been able to meet all indicators of students' mathematical communication ability.